Penerapan nilai iman, takwa dan akhlak mulia profil pelajar Pancasila dalam membentuk karakter islami siswa - A'yun, Qurroti; Pamungkas, M Bayu Akbar; Agustin, Intan Sintia Dewi; Zahroh, Imamah; Afandi, Rakhmad Galih; Zulkarnaen, Zulkarnaen (Tawazun: Jurnal Pendidikan Islam, 2023)
With the existence of an independent curriculum recently launched by the Minister of Education and Culture, various problems have not yet been found. There are quite prominent similarities between the curriculum compared to the previous curriculum, namely a study of the character or personality of students. The purpose of this study is to find out more about the Pancasila Student Profile which discusses the six main points of the Indonesian Pancasila Basic State. One of the six points is closely related to religion. These points are Faith, Piety to God Almighty, and Noble Morals which are related to the formation of the Islamic character of students. The author uses literature study or literature study to read, record, process data, and examine more deeply the first point of the independent curriculum. The results of this study indicate that the independent curriculum is related to Islamic religious education. Through the application of the Pancasila student profile, it is also expected to be able to shape the Islamic character of students in an era full of challenges of technological progress. The focus that will be discussed in this research is on the independent curriculum, Islamic personality, and the implementation of the independent curriculum which includes the first point of the Pancasila Student Profile. Faith, piety to God, and noble character are topics that are closely related to the Islamic character of students. And what is interesting from this research is that faith, piety, and noble character are topics that are very closely related to the Islamic character of students. Abstrak Dengan adanya kurikulum merdeka yang baru-baru ini diluncurkan Menetri Pendidikan dan Kebudayaan, ada berbagai problematika yang belum ditemukan titik terangnya. Terdapat kesamaan yang lumayan menonjol dari kurikulum tersebut dari pada kurikulum terdahulu, ialah ulasan mengenai karakter atau kepribadian peserta didik. Tujuannya dilakukan riset ini adalah guna mengenali lebih dalam tentang Profil Pelajar Pancasila yang didalamnya membahas tentang enam poin utama dari Dasar Negara Indonesia Pancasila. Satu dari enam poin tersebut berhubungan erat menjurus ke arah religious keagamaan. Poin tersebut ialah Beriman, Bertaqwa kepada Tuhan Yang Maha Esa dan Berakhlak Mulia yang berkaitan dengan pembentukan karakter islami siswa. Penulis menggunakan studi literatur atau studi kepustakaan untuk membaca, mencatat, mengolah data serta menelaah lebih jauh tentang kurikulum merdeka poin pertama. Hasil dari pembahasan ini menunjukkan bahwa kurikulum merdeka berkaitan dengan pendidikan agama Islam. Melalui penerapan profil pelajar Pancasila juga diharapkan bisa membentuk karakter islami siswa di era yang penuh dengan tantangan kemajuan teknologi. Fokus yang hendak dibahas dalam pembahasan ini menimpa kurikulum merdeka, kepribadian islami, serta menimpa aktivitas pelaksanaan kurikulum merdeka yang mencangkup poin pertama Profil Pelajar Pancasila. Beriman, bertaqwa kepada Tuhan dan berakhlak mulia ialah topik yang sangat berhubungan erat dengan karakter islami siswa. Serta yang jadi perihal menarik dari riset ini merupakan beriman, bertaqwa kepada Tuhan dan berakhlak mulia ialah topik yang sangat berhubungan erat dengan karakter islami siswa.